Application of Coloured Petri Nets for Veriﬁcation of Scenario Control Structures in UCM Notation - N. V. Vizovitin; V. A. Nepomniaschy; A. A. Stenenko (Моделирование и анализ информационных систем, 2016)
This article presents a method for the analysis and veriﬁcation of Use Case Maps (UCM) models with scenario control structures — protected components and failure handling constructs. UCM models are analyzed and veriﬁed with the help of coloured Petri nets (CPN) and the SPIN model checker. Algorithms for translating UCM scenario control structures into CPN and CPN into SPIN input language Promela are described. The number of elements of the resulting CPN model and the number of Promela model states are estimated. The presented algorithm and the veriﬁcation process are illustrated by the study of a network router ﬁrmware update.